How to Evaluate the Chemical Affinity of -OH and -COOH Functional Groups Toward U(VI) - Xuemei Cui; Xiaoying Xie; Yun Li; Yue Chen; Yan Ma; Shubin Yang (Molecules)
Which functional group shows a stronger affinity for U(VI) and can be introduced into material to enhance selective enrichment? This is crucial for U(VI) capture material design and evaluation. Following these questions, we herein compared and analyzed bare graphene, graphene oxide (GO), and carboxylated graphene oxide (GO-COOH) through experimental and theoretical calculations. Experiments show that U(VI) adsorption on GO-COOH (Qm = 344.1 mg/g) mainly occurs via inner-sphere complexation with the C=O group in -COOH. The -COOH group can significantly enhance the enrichment and selectivity of U(VI), and its affinity for U(VI) is greater than that of -OH. There is a strong interaction between [UO2(H2O)10]2+ and -COOH with an interaction energy of 1.13 eV. When U(VI) is adsorbed on GO, the original C-O(H) bond in GO breaks, leading to U(VI) seizing -OH and forming a more stable complex [UO2(H2O)10(OH)]1+. However, the desorption of U(VI) from GO is easier due to the weakened interaction between [UO2(H2O)10(OH)]1+ and GO after the C-O(H) bond breakage. Briefly, the combination of experimental observations and theoretical calculations provides a comprehensive understanding of the affinity and selectivity of -COOH and -OH for U(VI), and highlights the potential of using -COOH functionalization to enhance the U(VI) enrichment and separation performance of materials.